The Effect of Entrepreneurship Competency Education on Entrepreneurial Aspirations among Learners in Vocational Training Institutions - Atik Riyanti; Sujarwo Sujarwo; Yudan Hermawan (Education and Sociedad Journal, 2026)
This study aims to analyze the effect of the entrepreneurship skills education program on entrepreneurial interest among graduates of Course and Training Institution. Specifically, this study examines the influence of five PKW dimensions, namely recruitment and selection, learning and training, startup business mentoring, work equipment support, and marketing and partnership development, on entrepreneurial interest. This research employed a quantitative approach with an associative design. The population of this study consisted of 30 PKW graduates, all of whom were selected as the sample using a saturated sampling technique. Data were collected through a structured questionnaire measured on a five-point Likert scale. The research instrument was tested using validity and reliability tests, while the data were analyzed using multiple linear regression, coefficient of determination (R²), and partial t-tests. The results show that recruitment and selection, learning and training, work equipment support, and marketing and partnership development have a positive and significant effect on entrepreneurial interest. In contrast, startup business mentoring has a negative and statistically insignificant effect on entrepreneurial interest. The coefficient of determination indicates that the five dimensions of the PKW program explain 39.7% of the variance in entrepreneurial interest, while the remaining 60.3% is influenced by other factors outside the model. These findings suggest that the effectiveness of entrepreneurship education programs in vocational training institutions is not only determined by technical training, but also by the quality of participant selection, access to business equipment, and market-oriented support systems.